Practicing materiality - Van Dyke, Ruth M. (The University of Arizona Press, 2015)
"Practicing Materiality focuses on the job of applying materiality to anthropological investigations. It demonstrates a practical way to focus on the entangled lives of things without losing sight of their political and social implications"--Provided by publisher.